The Journey of Stars in Islamic Art A Critique on the Book Following the Stars: Images of the Zodiac in Islamic Art - Majid Behdani; Mohammad Khazayi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This text tries to criticize and analyze the book entitled “in following stars” and introduce it to individuals who are interested in the Islamic art field while it indicates the values and deficiencies of the book. The current work which is a booklet about the reflection of constellations in Islamic artworks has a valuable and significant title that is a very important subject in the studies of Islamic art. A subject that became artists’ concerns in the middle centuries of Islam and had allocated a huge mass of artistic motifs to itself. This book emphasizes the science of astronomy or astrology and in line with this so-called scientific process, has considered and analyzed motifs of twenty artistic objects that are kept in the Metropolitan Museum of New York. In this paper, to evaluate, approve, and correct the author's viewpoints, other researchers’ writings have been mentioned and used to supplement another point of view. Although the book has concept deficiencies and shortcomings, it has a novel and interesting subject and will be useful and desirable for researchers in the field of Islamic art.